ANALISIS KEHARMONISAN KELUARGA PERKAWINAN USIA DINI DI DESA SUNGAI SIALANG KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - Rosnita Rosnita '; Zahirman Zahirman '; Supentri Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: As humansbeings, a man cannot live alone that he needs other person in order to afford his needs of life. Since the human birth, man needs mother’s love. Day by day, his needs are increasing significantly and the smallest place to afford life is family. From this family group, a man will try to afford live both body and sprit. Familyis thepeople who are related by bloodor marriage consistin gof mother, father and children. In order to be able to run permanently and happily the couple that will marry must be totally ready for marriage and be able to take responsibility for the family. Therefore, it needs to consider whether the married couple who will have the appropriate or sufficient age to be married, as defined in the Lawon marriage No. 1 of 1974. The age of marriage for men and women is very important, for both the biological as well as psychological maturity. This research was conducted at Sungai Sialang village subdistrict Batu Hampar, regency Rokan Hilir. This research was conducted to determine how the family harmony marriage early ageat Sungai Sialang village subdistrict Batu Hampar regency Rokan Hilir. From theresults of the research anddiscussion on the analysis of the Harmony Family Marriage Early at Sungai Sialang village subdistrict Batu Hampar, regency Rokan Hilir in the category"Bad" because respondents who answered very often amount of0.33%. So it can be concluded that he Marriage Early at Sungai Sialang village subdistrict Batu Hampar regency Rokan Hilir disharmonious. The sampling techniqueused is purposive sampling with 30 people/respondents were sampled in this research. Data analysis techniques used is qualitative descriptive analysis.Keywords: Harmony Family, Marriage Early